Corporate governance in public sector enterprises - Dewan, S. M. (New Delhi : Pearson Longman, 2006)
With reference to Indian government business enterprises; contributed studies
Includes bibliographical references
Keywords: Corporate governance -- India; Government business enterprises -- India